2023
DOI: 10.3390/ijms241210199
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Effect of Dopamine and Dopaminergic Agonists as an Adjuvant Therapeutic Option in the Treatment of Cancer, Endometriosis, and Osteoarthritis

Julieta Griselda Mendoza-Torreblanca,
Noemi Cárdenas-Rodríguez,
Jazmín Carro-Rodríguez
et al.

Abstract: Dopamine (DA) and dopamine agonists (DA-Ag) have shown antiangiogenic potential through the vascular endothelial growth factor (VEGF) pathway. They inhibit VEGF and VEGF receptor 2 (VEGFR 2) functions through the dopamine receptor D2 (D2R), preventing important angiogenesis-related processes such as proliferation, migration, and vascular permeability. However, few studies have demonstrated the antiangiogenic mechanism and efficacy of DA and DA-Ag in diseases such as cancer, endometriosis, and osteoarthritis (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 185 publications
(271 reference statements)
0
1
0
Order By: Relevance
“…Cabergoline, a dopamine agonist, exerts anti-angiogenic effects by inducing endocytosis of VEGFR-2 in endothelial cells, leading to decreased and inactivated VEGF-VEGFR-2 binding ( 112 ). D2-ags are as powerful as standard anti-angiogenic compounds in interfering with angiogenesis and lesion size ( 111 , 113 ). In addition, in a prospective clinical trial, D2-ags were shown to be superior to luteinizing hormone-releasing hormone agonists in decreasing size of endometrial tumors, with fewer drug side effects, easier administration and lower price ( 112 ).…”
Section: Anti-angiogenic Treatment In Emmentioning
confidence: 99%
“…Cabergoline, a dopamine agonist, exerts anti-angiogenic effects by inducing endocytosis of VEGFR-2 in endothelial cells, leading to decreased and inactivated VEGF-VEGFR-2 binding ( 112 ). D2-ags are as powerful as standard anti-angiogenic compounds in interfering with angiogenesis and lesion size ( 111 , 113 ). In addition, in a prospective clinical trial, D2-ags were shown to be superior to luteinizing hormone-releasing hormone agonists in decreasing size of endometrial tumors, with fewer drug side effects, easier administration and lower price ( 112 ).…”
Section: Anti-angiogenic Treatment In Emmentioning
confidence: 99%